Lowly loaded carbon nanotubes induced high electrical conductivity and giant magnetoresistance in ethylene/1-octene copolymers. (26th October 2016) - Yan, Xingru; Gu, Junwei; Zheng, Guoqiang; Guo, Jiang; Galaska, Alexandra Maria; Yu, Jingfang; Khan, Mojammel Alam; Sun, Luyi; Young, David P.; Zhang, Qiuyu; Wei, Suying; Guo, Zhanhu
Abstract: High electrical conductivity in ethylene/1-octene copolymers (EOCs) was achieved by sticking CNTs onto the gelated EOCs pellet surface and the subsequent hot pressing. The electrical conductivity (σ) was observed to be dependent on the pressing temperature and the CNT loading. Variable range hopping (VRH) mechanistic study revealed a 3-d electron transport mechanism. Both unique positive and negative magnetoresistance (MR) phenomena were observed in these polymer nanocomposites (PNCs) and theoretically analyzed by two different models (wave-function shrinkage model for positive GMR vs. forward interference model for negative GMR). Other properties were tested and analyzed as well. Neat EOCs and their nanocomposites exhibited both Newtonian and shear thinning behaviors under melting state. Less internal chain-chain friction heat was generated than that of neat EOCs after applying the same oscillation frequencies. The increased thermal stability of EOC nanocomposites was observed with increasing the CNTs loading. An increased thermal conductivity ( λ ) was observed arising from the formed CNTs network. Graphical abstract: Highlights: Copolymer nanocomposites were prepared by coating carbon nanotubes on the surface of gelated polymer pellets. Electrical conductivity was observed to depend on the pressing temperature and CNT loading level. Variable range hopping (VRH) mechanistic study revealed a 3-d electron transport mechanism. Both unique positive and negative magnetoresistance (MR) phenomena were observed and analyzed by two different models.